Zúčastněné pozorování a rozhovor v terénní praxi - Marie Fritzová (AntropoWebzin)
This article is primarily based on ﬁeld research and interview, which are the main sources of data. I carried out this ﬁeld research between 2009 and 2012 in the West Bank. This ﬁeldwork was split into three stages (in 2009, 2010 and 2012). The method of participant observation and interviewing has a wide range of supporters as well as opponents among members of the scientiﬁc community. Participant observation and interviewing as basic anthropological research methods are often criticized for the subjective and ambiguous “microcosmic” perspective from which the surveyedproblemsareapproached.Nevertheless,theseare still important methods of data collection used in anthropology, and so the controversy about their use in practice is very important. Participant observation was the basic method that I applied in my ﬁeld research. Since I spent a lot of time with my informants, I won their trust, which is necessary for the successful use of this method. I participated in routine communication between members of a household, but I could watch the little quarrels, debates, disputes, etc. Thanks to the method of participant observation, I was able to discover the inner world of the surveyed communities. Which obstacles are encountered in practice in my ﬁeld research, and how can participant observation and interviewing be of use in practice? This is the fundamental question I try to answer in this article.